Implementation of Good Governance in the Provincial Government of the Special Capital Region of Jakarta - Putra, Satria Kurniawan; Irawan, Anang Dony (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
The purpose of this research is to determine the implementation of the General Principles of Good Government in the government of the Special Capital Region of Jakarta Province and to examine the inhibiting factors in implementing the General Principles of Good Government in the government of the Special Capital Region of Jakarta Province. This research is normative juridical in nature, the approach taken includes a statutory approach. The collected data was analyzed descriptively qualitatively. The results of the research conclude that, first, the administration of the Special Capital Region of Jakarta Province has implemented the General Principles of Good Government as guidelines in preparing licensing policies in the Province of the Special Capital Region of Jakarta, as outlined in Regional Regulation Number 5 of 2014 concerning Transportation and Governor Regulation 52 2022 concerning amendments to DKI Jakarta Governor Regulation Number 20 of 2019 concerning Assignments to Jakarta Transportation Limited Liability Companies for the Development, Revitalization, Operation and Maintenance of Bus Stops and Other Supporting Facilities in the Context of Public Transportation Integration. Second, the inhibiting factor in the implementation of the Provincial Government of the Special Capital Region of Jakarta is the quality of human resources in the State Civil Apparatus, more specifically, namely the lack of understanding of technology. Keyword: General Principles of Government; Policy Implementation; Provincial Government of the Special Capital Region of Jakarta.